Development geography - Hodder, Rupert (Routledge contemporary human geography series., 2000)
Annotation Development Geographyis an informative and vibrant introductory level text, with a wealth of contrasting case-studies and illustrations. Written to stimulate critical thought and discussion about development, it does not assume any clear-cut distinction between 'developed' and 'developing' parts of the world. Case-studies highlight the problems and possible solutions at local, national and international scales. These include:* food production in Senegal* Disney in China* Hurricane Mitch in Honduras* corruption in Bulgaria* further studies from Russia, Bangladesh and Vietnam. Development Geographyis the fifth book to be published in the popular modular text series Routledge Contemporary Human Geography.